UNWRAPPING ISOCHROMATIC BY COMBINING WHITE LIGHT PHOTOELASTICITY WITH PHASE SHIFTING THCHNOLOGY - LIU XiaoMeng; DAI ShuGuang (Jixie qiangdu)
Use of a color code to identify fringe orders has been in use in conventional photoelasticity. Phase shifting technology is the most widely used for isochromatic evaluation due to its simplicity and accuracy. The phase shifting method obtain isochromatic only in a wrapped form. On the one hand the colors tend to merge beyond fringe order three in white light photoelasticity,and on the other phase unwrapping is a challenging issue. Due to the fact that the isochromatic fringes are continuously varying in fringe patterns,the white light photoelasticity and the phase shifting technique are adapted to determine the isochromatic fringe orders. The advantage of new approach allows for determination of isochromatic fringe orders regardless whether the zero-order fringe is present or not. Experimental demonstration was performed on a disc under compressive loading.